2016
DOI: 10.1002/ece3.2671
|View full text |Cite
|
Sign up to set email alerts
|

Can spatial sorting associated with spawning migration explain evolution of body size and vertebral number inAnguillaeels?

Abstract: Spatial sorting is a process that can contribute to microevolutionary change by assembling phenotypes through space, owing to nonrandom dispersal. Here we first build upon and develop the “neutral” version of the spatial sorting hypothesis by arguing that in systems that are not characterized by repeated range expansions, the evolutionary effects of variation in dispersal capacity and assortative mating might not be independent of but interact with natural selection. In addition to generating assortative matin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…Species showing pronounced intraspecific variation include some salmonids (S. trutta), the three-spine stickleback (Gasterosteus aculeatus), and the northern pike (Esox lucius) in which different populations of the same species can be classified as belonging to at least two of the oceanodromous, potamodromous, and the anadromous lifestyles (Jonsson and Jonsson, 1993;Fleming, 1996;Lucas and Baras, 2001;Dodson et al, 2013;Forsman et al, 2015;Leitwein et al, 2016). There is also extensive variation in timing and distance of migration among species and populations (McDowall, 1997;Hendry and Day, 2005;Kuparinen and Merilä, 2009;Griffiths, 2010;Seamons and Quinn, 2010;Kovach et al, 2015;Forsman and Berggren, 2017;Bloom et al, 2018).…”
Section: Main Migration Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…Species showing pronounced intraspecific variation include some salmonids (S. trutta), the three-spine stickleback (Gasterosteus aculeatus), and the northern pike (Esox lucius) in which different populations of the same species can be classified as belonging to at least two of the oceanodromous, potamodromous, and the anadromous lifestyles (Jonsson and Jonsson, 1993;Fleming, 1996;Lucas and Baras, 2001;Dodson et al, 2013;Forsman et al, 2015;Leitwein et al, 2016). There is also extensive variation in timing and distance of migration among species and populations (McDowall, 1997;Hendry and Day, 2005;Kuparinen and Merilä, 2009;Griffiths, 2010;Seamons and Quinn, 2010;Kovach et al, 2015;Forsman and Berggren, 2017;Bloom et al, 2018).…”
Section: Main Migration Modesmentioning
confidence: 99%
“…Patterns and strategies of migration vary extensively among species with regards to function (e.g., spawning, feeding, and refuge from predators and other environmental stressors), migration mode (diadromous, potamodromous and oceanodromous), mode of parity (semelparous-iteroparous), timing of migratory events (phenology), and migratory distance (McDowall, 1997;Griffiths, 2010;Seamons and Quinn, 2010;Mehner, 2012;Forsman and Berggren, 2017;Nilsson et al, 2019). As for diadromy, inter-specific comparisons have uncovered that anadromous species predominate in temperate latitudes where productivity in freshwater is generally lower than in marine environments whereas catadromy dominates in tropical latitudes where the highest productivity is found in freshwater habitats (Gross et al, 1988;McDowall, 1997).…”
Section: Variation Among Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to identify proxies for dispersal capacity is to use indirect estimates based on traits that are thought, or proven, to be associated with differences in dispersal capacity. Earlier studies have indicated a number of species traits and ecological characteristics as related to dispersal capacity in a wide range of organisms, such as hind-foot length in voles (Forsman, Merilä, & Ebenhard, 2011;Shine, Brown, & Phillips, 2011), wing length in birds and insects (Berggren, Tinnert, & Forsman, 2012;Rundle, Bilton, Abbott, & Foggo, 2007;Sekar, 2012;Stevens et al, 2010), and body size in eels (Forsman & Berggren, 2017).…”
mentioning
confidence: 99%
“…Despite its potential role in micro‐ and macro‐evolutionary processes and the increasing recognition that genotypes can differ in dispersal ability or in habitat preference (Rice, ; Canestrelli et al., ; Forsman & Berggren, ), habitat choice is still an overlooked issue in evolutionary ecology (Edelaar et al., ). Indeed, habitat choice has been rarely evoked to explain the genetic patterns of natural populations (e.g., Byers, , ; Borowsky, ; Szarowska, Falniowski, Mazan, & Fialkowski, ), likely because field studies make it difficult to disentangle the patterns of genetic divergence originated by habitat choice from those due to the action of other diverging forces, such as drift or selection.…”
Section: Introductionmentioning
confidence: 99%